Preparation method and application of low-load RuPdPt ternary noble metal electrocatalyst

The RuPdPt-NixFeyCuzOOH catalyst is prepared by a simple and fast method, which solves the problem of complex, time-consuming and energy-consuming preparation process of precious metal-based electrocatalysts, and realizes large-scale preparation and the formation of single-atom-cluster structures, which improves the stability and activity of the catalyst.

CN119877029APending Publication Date: 2025-04-25CHINA THREE GORGES UNIV

Patent Information

Application Number
CN202510236137.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The preparation process of existing precious metal (Ru, Pd, Pt)-based electrocatalysts is complex, time-consuming and energy-consuming, and expensive, and it is impossible to achieve controllable synthesis at the single-atom-cluster scale, and the catalyst is insufficient under industrial operating conditions (greater than 400 mA cm-2 and 50°C).

Method used

A low-load RuPdPt ternary noble metal electrocatalyst is used to form a NixFeyCuzOOH substrate by etching the foam nickel foam and soaking it in a mixed solution containing iron chloride, copper chloride and sodium chloride, and then immersing it in a mixture of precious metals. After stirring and heating treatment, the RuPdPt-NixFeyCuzOOH composite catalyst is formed.

Benefits of technology

Large-scale and large-scale preparation of RuPdPt ternary precious metal catalyst was achieved. The catalyst exhibited a single-atom-cluster composite structure, which improved the atomic utilization rate of precious metals, and maintained stability for more than 1,000 hours under the current density of 500 mA cm-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877029A_ABST
    Figure CN119877029A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a low-load RuPdPt ternary noble metal electrocatalyst. The preparation method comprises the following steps: etching foamed nickel in a hydrochloric acid solution, and soaking the etched foamed nickel in a mixed solution containing ferric chloride, copper chloride and sodium chloride for 3-12 hours to obtain a NixFeyCuzOOH substrate; ruthenium salt, platinum salt and palladium salt are mixed and then ground, water is added to prepare a mixed solution, then an alcoholic solution of dimethylglyoxime disodium salt octahydrate is added, and a precious metal mixed solution is formed after ultrasonic dispersion; the preparation method comprises the following steps: soaking a NixFeyCuzOOH substrate in a noble metal mixed solution, soaking for 1-6 hours under stirring and heating conditions, washing an obtained product with water, and drying to obtain the RuPdPt-NixFeyCuzOOH composite catalyst. According to the invention, the noble metals Ru, Pd and Pt are combined with the substrate NixFeyCuzOOH nanosheets through M1-M2-O bonds, so that monatomic-cluster sites of the noble metals Ru, Pd and Pt are effectively anchored, and the stability of the catalyst at high current density is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a preparation method of a low-loaded RuPdPt ternary electrocatalyst and an application thereof in a hydrogen evolution reaction by electrolysis of water. Background Art

[0002] At present, the preparation process of precious metal (Ru, Pd, Pt)-based catalysts usually requires the use of complex processes such as high-temperature hydrothermal method, electrodeposition, centrifugation, drying, etc. to obtain powder samples, and additional high-temperature calcination is required to improve the catalytic performance. In addition, the prepared precious metal (Ru, Pd, Pt)-based catalysts only present nano / micron-scale microstructures, and cannot achieve controllable synthesis at the single atom-cluster scale and the yield is extremely low. More importantly, the synthesis of precious metal (Ru, Pd, Pt)-based catalysts has extremely high requirements for preparation conditions and equipment, and the preparation process is cumbersome, time-consuming and energy-consuming, making it difficult to be used on a large scale in industry. For example, in the patent "RuNi alloy nanocomposite materials, preparation methods and applications thereof", the RuNi catalyst needs to be annealed at 300 to 1000 ° C in an inert atmosphere. This additional protective gas and energy-consuming annealing process greatly increase the cost of preparation and is difficult to apply on a large scale. In the patent "A RuNi-LDHs electrocatalyst and its preparation method and application", the Ru-based catalyst requires the use of sodium borohydride, a hazardous chemical, and requires 2-24 hours and complex processes such as centrifugation, cleaning, filtration, and vacuum drying to obtain a powder sample. The prepared sample is a nanoscale nanosheet structure. In general, the current precious metal (Ru, Pd, Pt)-based electrocatalysts have the problems of complex preparation process, time-consuming and energy-consuming, high synthesis cost, and inability to achieve atomic-cluster scale preparation. In addition, the performance test of the catalyst is only carried out at a small current density (10-100 mA cm -2 ) conditions, and cannot truly reflect the catalyst under industrial operating conditions (greater than 400 mA cm -2 and 50°C) to achieve long-term stability. Summary of the invention

[0003] The objects of the present invention are as follows: (1) The problems of the preparation process of precious metal (Ru, Pd, Pt) based electrocatalysts, such as complicated, high cost, long time consumption and high equipment requirements, were solved, and the large-scale and large-size preparation of RuPdPt ternary precious metal catalysts was realized.

[0004] (2) The consistent, uniform, and reproducible preparation of large-scale electrocatalysts is achieved, and the prepared catalysts present a single atom-cluster composite structure, which greatly improves the atomic utilization of precious metals (Ru, Pd, Pt).

[0005] (3) Improve the stability and catalytic activity of the catalyst in the hydrogen production reaction by water electrolysis under industrial operating conditions. -2 Under the condition of stable operation, it can run stably for more than 1000 hours.

[0006] A method for preparing a low-load RuPdPt ternary noble metal electrocatalyst comprises the following steps: (1) After etching the nickel foam in a hydrochloric acid solution, the foam is then immersed in a mixed solution containing ferric chloride, copper chloride and sodium chloride for 3-12 hours to obtain Ni x Fe y Cu z OOH substrate; (2) mixing ruthenium salt, platinum salt and palladium salt and grinding them, adding water to prepare a mixed solution, adding an alcohol solution of dimethylglyoxime disodium salt octahydrate, and ultrasonically dispersing them to form a noble metal mixed solution; (3) Ni x Fe y Cu z The OOH substrate is immersed in a noble metal mixed solution, stirred and heated for 1-6 hours, and the obtained product is washed with water and dried to obtain RuPdPt-Ni x Fe y Cu z OOH composite catalyst.

[0007] The concentration of the hydrochloric acid solution in step (1) is 0.5-2 mol / L; The mass concentrations of ferric chloride, cupric chloride and sodium chloride are 0.02-0.2 g / ml, 0.001-0.2 g / ml and 0.001-0.05 g / ml respectively.

[0008] After immersion, a layer of Ni is formed in situ on the surface of nickel foam. x Fe y Cu z OOH material, as a nanoarray, provides a large specific surface area for the loading of RuPdPt single atom-clusters, making the loading more uniform and less prone to agglomeration.

[0009] In the step (2), the concentration of the ruthenium salt in the mixed solution is 0.1-1 mol / L, the concentration of the platinum salt is 0.01-1 mol / L, and the concentration of the palladium salt is 0.01-1 mol / L.

[0010] The concentration of the alcohol solution of dimethylglyoxime disodium salt octahydrate is 0.2-5 mol / L.

[0011] The solution will react with ruthenium salt, platinum salt and palladium salt, so that ruthenium, platinum and palladium are dissolved and better dispersed, paving the way for the subsequent formation of single atom-clusters.

[0012] The ultrasonic dispersion time in step (2) is 0.5-2h.

[0013] In the step (3), the stirring speed is 300-1200 rpm and the heating temperature is 45-80°C.

[0014] The purpose of heating is to make ruthenium, platinum and palladium react faster in the solution to form single atom clusters, while the purpose of stirring is to make the formed single atom clusters more evenly dispersed in the Ni x Fe y Cu z The OOH support ensures the uniformity of the preparation of the electrocatalyst, while preventing agglomeration and maintaining the configuration of metal single atoms-clusters.

[0015] The drying is vacuum drying, and the drying conditions are drying at 100-250° C. for 3-12 hours.

[0016] The low-loaded RuPdPt ternary noble metal electrocatalyst prepared by the method described above exists in the form of a single atom-cluster. For example, the Ru element contains a characteristic peak located near 2.7Å in the R-space spectrum, which corresponds to the Ru-OM bond. The Ru single atom-cluster and Ni x Fe y Cu z OOH is combined in the form of chemical bonds.

[0017] A water electrolysis hydrogen evolution material comprises a low-loaded RuPdPt ternary noble metal electrocatalyst prepared by the method.

[0018] The preparation process is simple and fast, does not require cumbersome processes (such as electrodeposition, high-temperature calcination, and high-tech and expensive preparation technology), can achieve large-scale and large-size preparation of catalysts, and the prepared catalysts present a noble metal single atom-cluster structure, which greatly improves the atomic utilization of noble metals (Ru, Pd, Pt), which is also one of the important highlights of this preparation method that distinguishes it from other noble metal (Ru, Pd, Pt)-based catalysts. The large-size Ru single atom-cluster catalyst has uniformity, consistency, and repeatability in nanostructure and catalytic performance, and exhibits excellent activity and stability in the hydrogen evolution reaction. At a current density of 10 mA cm -2 The overpotential is only 5 mV, and it can be used at a high current density of 500 mA cm -2 It can run stably for more than 1000 hours under the specified conditions.

[0019] At present, the preparation process of precious metal (Ru, Pd, Pt)-based catalysts usually requires the use of complex processes such as hydrothermal method, electrodeposition, centrifugation, drying, etc. to obtain powder samples, and requires additional heating or high-temperature calcination to improve catalytic performance. In addition, the prepared precious metal (Ru, Pd, Pt)-based catalysts only present nano / micron-scale microstructures, and cannot achieve controllable synthesis at the single atom-cluster scale and the yield is extremely low. More importantly, the synthesis of precious metal (Ru, Pd, Pt)-based catalysts has extremely high requirements for preparation conditions and equipment. The preparation process is cumbersome, time-consuming and energy-consuming, and it is difficult to be used on a large scale in industry.

[0020] In general, current noble metal (Ru, Pd, Pt) based electrocatalysts have the problems of complex preparation process, time-consuming and energy-consuming, high synthesis cost, and inability to achieve atomic-cluster scale preparation. In addition, the performance test of the catalyst is only carried out at a small current density (10-100 mA cm -2 ) conditions, and cannot truly reflect the catalyst under industrial operating conditions (greater than 400 mA cm -2 and 50°C) to achieve long-term stability.

[0021] The key point of this scheme is that the preparation method is simple and fast. It can prepare noble metal (Ru, Pd, Pt) single atom-cluster electrocatalysts without complicated preparation process and expensive cost, which greatly improves the atomic utilization rate and catalytic activity of noble metals (Ru, Pd, Pt). x Fe y Cu z OOH nanosheets through M 1 -M 2 -O bonds are combined to effectively anchor the noble metal (Ru, Pd, Pt) single atom-cluster sites, greatly improving the stability of the catalyst at high current density.

[0022] Technical Effects The present invention realizes RuPdPt-Ni by a simple and quick method x Fe y Cu z OOH catalyst 600 cm 2 The catalyst can be prepared on a large scale (the preparation size can be further expanded by enlarging the preparation container), and the catalyst has excellent catalytic performance and microstructural consistency, which can realize large-scale preparation of the catalyst on an industrial scale.

[0023] Preparation of RuPdPt-Ni x Fe y Cu zOOH catalysts have a fine structure of Ru, Pd, and Pt single atoms-clusters, which is beneficial to the utilization of precious metal atoms and the exposure of active sites. x Fe y Cu z The chemical bonds between OOH groups can enhance interfacial electron transfer and improve the overall stability of the catalyst at high current density.

[0024] Preparation of RuPdPt-Ni by the method of the present invention x Fe y Cu z The OOH catalyst has a simple process, low energy and time consumption, and is easy to prepare on a large scale and promote industrialization. The self-supporting catalyst exhibits good catalytic performance in the hydrogen evolution reaction and has good practical application prospects in the fields of water electrolysis and metal-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 .RuPdPt-Ni x Fe y Cu z Schematic diagram of the preparation of OOH catalyst.

[0026] Figure 2 .RuPdPt-Ni x Fe y Cu z Actual picture of large-scale preparation of OOH catalyst.

[0027] Figure 3 .RuPdPt-Ni x Fe y Cu z Spherical aberration electron microscope image of OOH catalyst.

[0028] Figure 4 . X-ray absorption fine structure of RuPdPt-Ni x Fe y Cu z R-space map of Ru element in OOH catalyst.

[0029] Figure 5 .RuPdPt-Ni x Fe y Cu z OOH and Ni x Fe y Cu z Linear sweep voltammetry curve of OOH.

[0030] Figure 6 .RuPdPt-Ni xFe y Cu z OOH at a current density of 500 mA cm -2 Stability test during operation.

[0031] Figure 7 . Impedance spectra of various types of catalysts.

[0032] Figure 8 . Precious Metal 40% Pt / C / / IrO 2 and RuPdPt-Ni x Fe y Cu z OOH / / Ni x Fe y Cu z Comparison of water splitting performance of OOH electrolyzer. DETAILED DESCRIPTION

[0033] Example 1 First, commercial nickel foam was placed in a 0.5-2 mol / L hydrochloric acid solution for 30 minutes, and then the nickel foam was immersed in a 20 ml deionized water mixed solution containing 2.0 g ferric chloride, 2.0 g copper chloride and 0.5 g sodium chloride for 6 hours to obtain Ni x Fe y Cu z OOH substrate.

[0034] Mix ruthenium chloride, potassium chloroplatinate, and potassium chloroargon palladium acid reagents and grind them in a mortar for 0.5-2 hours to obtain a uniform powder reagent, and then prepare a mixed solution A containing 0.5 mol / L ruthenium chloride, 0.5 mol / L potassium chloroplatinate, and 0.5 mol / L potassium chloroargon palladium acid; Then, 0.2 mol of dimethylglyoxime disodium salt octahydrate was dissolved in 50 ml of ethanol to form solution B. Solution A and solution B were mixed and ultrasonicated in a cell crusher for 0.5-2 hours to obtain a uniform solution C.

[0035] Then, Ni x Fe y Cu z The OOH substrate was immersed in solution C for 2 hours. In order to uniformly load the noble metal atoms, the solution was stirred at 800 rpm and heated in an oil bath at 45-80°C. After that, the washed and dried sample was placed in a vacuum drying oven at 100-120°C for 5 hours to achieve the anchoring of the noble metal single atom-cluster firmly on the Ni x Fe y Cu z OOH substrate. After vacuum drying, RuPdPt-Ni x Fey Cu z OOH composite catalyst.

[0036] RuPdPt-Ni x Fe y Cu z Schematic diagram of the preparation of OOH catalyst Figure 1 As shown in Figure 2, nickel foam forms Ni after being immersed in a corrosion solution containing Fe, Cu, Na and Cl ions. x Fe y Cu z OOH substrate, and then reacted with a mixed solution of ruthenium chloride, potassium chloroplatinate and potassium chloroargon palladium to obtain RuPdPt-Ni x Fe y Cu z OOH self-supported large-scale catalyst electrode.

[0037] The physical object prepared by the technical solution of the present invention is as follows Figure 2 As shown, it is a RuPdPt-Ni x Fe y Cu z Large-scale physical picture of OOH composite catalyst.

[0038] A simple method was used to achieve a catalyst with a wavelength of 600 cm 2 The large-scale preparation (if the preparation container is enlarged, the size can be easily expanded further), and the color of each part is consistent, which shows the consistency of the composition and structural properties of the catalyst.

[0039] RuPdPt-Ni x Fe y Cu z Spherical aberration electron microscope image of OOH catalyst Figure 3 As shown in the figure, the results of spherical aberration electron microscopy show that the noble metals Ru, Pd, and Pt exist in the form of single atom-clusters, which effectively reduces the use of noble metals Ru, Pd, and Pt and improves the utilization rate of unit Ru, Pd, and Pt atoms.

[0040] Similarly, too low a stirring speed (200 rpm) will cause the formed substance to form floccules at the bottom of the solution, making it difficult to load on the Ni x Fe y Cu z On the OOH, a high stirring speed (1500 rpm) will cause a water vortex to form in the middle of the solution, which also prevents the noble metals ruthenium, palladium, and platinum from being evenly loaded on the Ni x Fe y Cu z On OOH.

[0041] X-ray absorption fine structure of RuPdPt-Ni x Fe y Cu z The R-space spectrum of Ru element in OOH catalyst is as follows Figure 4 shown.

[0042] Fine structure of RuPdPt-Ni from X-ray absorption x Fe y Cu z The R-space spectrum of Ru element in OOH catalyst shows that the characteristic peak at about 2.7Å corresponds to the Ru-OM bond, which shows the Ru single atom-cluster and Ni x Fe y Cu z OOH is combined in a chemical bond manner, which helps to improve the interfacial electron transfer efficiency and overall stability of the catalyst.

[0043] When the concentration of dimethylglyoxime disodium salt is low (such as 0.1 mol / L), the solution formed is difficult to react quickly with ruthenium salt, palladium salt, and platinum salt, which makes the preparation process time-consuming and the precious metals ruthenium, palladium, and platinum are difficult to be uniformly loaded on Ni. x Fe y Cu z OOH, while high concentration will cause ruthenium, palladium and platinum to agglomerate, making it difficult to form a single atom-cluster configuration.

[0044] The self-supporting RuPdPt-Ni x Fe y Cu z OOH catalyst was used as the working electrode, carbon rod as the counter electrode, and Hg / HgO as the reference electrode to form a three-electrode electrolytic cell. The electrolyte was 1 M potassium hydroxide solution. The electrolytic cell was connected to the electrochemical workstation to ensure good electrode contact. The linear sweep voltammetry test program was used to test in the voltage range of -0.5V to -1.5V, with a scan rate of 5 mV / s, and the current density versus potential curve was recorded to evaluate the hydrogen evolution activity of the catalyst.

[0045] RuPdPt-Ni x Fe y Cu z OOH and Ni x Fe y Cu z The linear sweep voltammetry curve of OOH substrate is shown in Figure 5 shown.

[0046] From RuPdPt-Ni x Fe y Cu z OOH and Ni x Fey Cu z The linear sweep voltammetry curves of OOH substrates show that Ru, Pd, and Pt single atom-clusters modify Ni x Fe y Cu z OOH greatly improves its activity in hydrogen evolution reaction. -2 The overpotential is only 5 mV, and it also exhibits excellent catalytic performance at high current density.

[0047] The self-supporting RuPdPt-Ni x Fe y Cu z OOH catalyst was used as the working electrode, carbon rod as the counter electrode, and Hg / HgO as the reference electrode to form a three-electrode electrolytic cell. The electrolyte was 1 M potassium hydroxide solution. The electrolytic cell was connected to the electrochemical workstation to ensure good electrode contact. The stability test was performed by chronoamperometry with a test current of 500 mA cm -2 , the voltage range is between -0.5 and -1.5V, the current retention rate of the catalyst during long-term operation is analyzed and the stability of the catalyst is evaluated.

[0048] RuPdPt-Ni x Fe y Cu z OOH at a current density of 500 mA cm -2 The stability test is as follows: Figure 6 shown.

[0049] RuPdPt-Ni x Fe y Cu z OOH at a current density of 500 mA cm -2 The RuPdPt-Ni x Fe y Cu z OOH has excellent stability and is more suitable for high current density hydrogen evolution reaction under working conditions.

[0050] The self-supporting RuPdPt-Ni x Fe y Cu zOOH catalyst was used as the working electrode, carbon rod as the counter electrode, and Hg / HgO as the reference electrode to form a three-electrode electrolytic cell, and the electrolyte was 1 M potassium hydroxide solution. The electrolytic cell was connected to the electrochemical workstation to ensure good electrode contact. In the electrochemical workstation software, the "Electrochemical Impedance Spectroscopy (EIS)" mode was selected, and a small amplitude sinusoidal potential of 10 mV was applied, with a frequency from high frequency 100 KHz to low frequency 0.01 Hz, and impedance analysis was performed on the tested spectrum.

[0051] Impedance spectra of various types of catalysts such as Figure 7 Based on the impedance spectrum, it can be seen that RuPdPt-Ni x Fe y Cu z OOH has the smallest electron transfer impedance, which explains the x Fe y Cu z OOH has faster reaction kinetics during the hydrogen evolution reaction and can achieve rapid electron transfer.

[0052] The self-supporting RuPdPt-Ni x Fe y Cu z OOH catalyst and Ni x Fe y Cu z OOH was used as the cathode and anode of the electrolytic cell to form a two-electrode electrolytic cell, and the electrolyte was 1 M potassium hydroxide solution. The electrolytic cell was connected to the electrochemical workstation to ensure good electrode contact. The linear sweep voltammetry test program was used to test in the voltage range of 0.5V to 2V, with a scan rate of 2mV / s, and the current density versus potential curve was recorded to evaluate the catalyst's overall water splitting performance. 40% Pt / C / / IrO 2 During the test, 10 mg of 40% Pt / C or IrO 2 5 mg of carbon black and 50 μl of Nafion solution were added to 1000 μl of ethanol solution and ultrasonically treated to prepare catalyst slurry. The catalyst slurry was evenly coated on the nickel foam and dried to obtain a working electrode. Other test methods were similar to the above.

[0053] Precious Metal 40% Pt / C / / IrO 2 and RuPdPt-Ni x Fe y Cu z OOH / / Ni x Fe y Cu zComparison of water splitting performance of OOH electrolyzer Figure 8 shown.

[0054] From precious metals 40% Pt / C / / IrO 2 and RuPdPt-Ni x Fe y Cu z OOH / / Ni x Fe y Cu z The linear sweep voltammetric curve of the OOH electrolytic cell for water decomposition shows that RuPdPt-Ni x Fe y Cu z OOH / / Ni x Fe y Cu z The overall water splitting performance of OOH electrolyzer is far better than that of precious metal 40% Pt / C / / IrO 2 The performance of the RuPdPt-Ni electrolyzer is more obvious, especially at high current density, indicating that x Fe y Cu z OOH catalysts have great application prospects.

Claims

1. A method for preparing a low-load RuPdPt ternary noble metal electrocatalyst, characterized in that: The steps include: (1) After etching the nickel foam in a hydrochloric acid solution, the foam is then immersed in a mixed solution containing ferric chloride, copper chloride and sodium chloride for 3-12 hours to obtain Ni x Fe y Cu z OOH substrate; (2) mixing ruthenium salt, platinum salt and palladium salt and grinding them, adding water to prepare a mixed solution, adding an alcohol solution of dimethylglyoxime disodium salt octahydrate, and ultrasonically dispersing them to form a noble metal mixed solution; (3) Ni x Fe y Cu z The OOH substrate is immersed in a noble metal mixed solution and immersed for 1-6 hours under stirring and heating conditions. The obtained product is washed with water and dried to obtain RuPdPt-Ni x Fe y Cu z OOH composite catalyst.

2. The method for preparing a low-load RuPdPt ternary noble metal electrocatalyst according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step (1) is 0.5-2 mol / L; The mass concentrations of ferric chloride, cupric chloride and sodium chloride are 0.02-0.2 g / ml, 0.001-0.2 g / ml and 0.001-0.05 g / ml respectively.

3. The method for preparing a low-load RuPdPt ternary noble metal electrocatalyst according to claim 1, characterized in that: In step (2), the concentration of the ruthenium salt in the mixed solution is 0.1-1 mol / L, the concentration of the platinum salt is 0.01-1 mol / L, and the concentration of the palladium salt is 0.01-1 mol / L.

4. The method for preparing a low-load RuPdPt ternary noble metal electrocatalyst according to claim 3, characterized in that: The concentration of the alcohol solution of dimethylglyoxime disodium salt octahydrate is 0.2-5 mol / L.

5. The method for preparing a low-load RuPdPt ternary noble metal electrocatalyst according to claim 4, characterized in that: The ultrasonic dispersion time in step (2) is 0.5-2h.

6. The method for preparing a low-load RuPdPt ternary noble metal electrocatalyst according to claim 1, characterized in that: The stirring speed is 300-1200 rpm and the heating temperature is 45-80°C.

7. The method for preparing a low-load RuPdPt ternary noble metal electrocatalyst according to claim 1, characterized in that: The drying is vacuum drying, and the drying conditions are drying at 100-250° C. for 3-12 hours.

8. A low-loaded RuPdPt ternary noble metal electrocatalyst prepared by the method according to any one of claims 1 to 7, wherein the catalyst exists in the form of a single atom-cluster.

9. Application of a low-loading RuPdPt ternary precious metal electrocatalyst in hydrogen evolution by water electrolysis.

10. A material for hydrogen evolution by electrolysis of water, comprising a low-loaded RuPdPt ternary noble metal electrocatalyst prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Electrolyzed water catalyst and preparation method thereof

    CN115679365A

  • Preparation method of bifunctional electrolyzed water catalyst with high-activity array structure

    CN115852432A

Cited By

  • Pt-Au catalytic electrode and preparation method and application thereof

    CN121781184A